2018
DOI: 10.1021/acs.iecr.8b02295
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Non-Food-Based Diesel Fuels and Base Oils

Abstract: The importance of aliphatic fuel and base oil blending components produced on a nonpetroleum basis is increasing. Therefore, the possibility to produce these environmentally friendly products in new catalytic ways was studied. High molecular weight Fischer−Tropsch waxes synthesized from lignocellulose-based synthesis gas, waste fatty acids, and different triglycerides were converted to diesel fuels and base oils over NiMoP/Al 2 O 3 and Pt/SAPO-11 catalysts. The optimal operating parameters of high-quality prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Liu et al 27 prepared SAPO-11 with a mesopore size distribution in the range of 6−8 nm and applied it to the alkylation of naphthalene with methanol. Hollóet al 28 found that Pt/SAPO-11 catalysts synthesized using aluminum acetate or basic aluminum acetate as the aluminum source had different pore structures and a mesopore volume of 0.12 cm 3 / g. The catalyst was used in the hydrocracking/isomerization of bioalkanes, resulting in either monobranched or multibranched alkanes. Kasza et al 29 studied the isomerization of bioparaffin added to fatty acids on a Pt/SAPO-11 catalyst with a Brunauer−Emmett−Teller (BET) specific surface area of 105 m 2 /g and both a micro-and mesoporous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 27 prepared SAPO-11 with a mesopore size distribution in the range of 6−8 nm and applied it to the alkylation of naphthalene with methanol. Hollóet al 28 found that Pt/SAPO-11 catalysts synthesized using aluminum acetate or basic aluminum acetate as the aluminum source had different pore structures and a mesopore volume of 0.12 cm 3 / g. The catalyst was used in the hydrocracking/isomerization of bioalkanes, resulting in either monobranched or multibranched alkanes. Kasza et al 29 studied the isomerization of bioparaffin added to fatty acids on a Pt/SAPO-11 catalyst with a Brunauer−Emmett−Teller (BET) specific surface area of 105 m 2 /g and both a micro-and mesoporous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among the biomass feedstocks, fats have such advantageous characteristics of liquids and structures with long alkyl chains that they can be transformed to fuels of gasoline, kerosine, and gas oil; aromatics; and hydrogen. Although transesterification with methanol provides biodiesel fuels, reactants such as glycerol, surplus methanol, and catalysts remain in the final stage of the reaction and have to be removed prior to their utilization. Meanwhile, heterogeneous transesterification making fatty acid methyl ester (FAME), catalytic cracking making gasoline, propylene, and aromatics for petrochemicals, and hydrotreating of fats to biodiesel fuels with high cetane numbers and bio-jet fuels , have already been reported during the last decade. Among them, the hydrotreating of fats gives not only vehicle fuels, C3 fraction, and light gas oil with the higher durability for oxidation than that of FAME but also raw materials for petrochemicals, especially aromatics. For example, after treatment of fats by ZSM-5 with mesopore and macropore at 300 °C and pressure up to and including 4.0 MPa, hydrotreatment of the oils obtained was performed using NiMo/Al 2 O 3 at 340 °C and 4.5 MPa. , The two-step process using ZSM-5 with a 0.6 cm 3 /g pore volume at a high pressure gave 25–29 wt % n -paraffin and 8–15 wt % aromatics, whereas aromatics were not given by ZSM-5 with 0.35 cm 3 /g pore volume.…”
Section: Introductionmentioning
confidence: 99%